ANALISIS NILAI SOSIAL DALAM MANTRA PENGOBATAN MASYARAKAT MELAYU DESA MEPAR KECAMATAN LINGGA KABUPATEN LINGGA - Amelia, Rizki; Irawan, Dody; Habiba, Siti; Wahyusari, Ahada; Wardana, Musliha; Zaitun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the social values contained in the healing mantras of the Malay community of Mepar Village, Lingga District, Lingga Regency. The purpose of this study is to describe the social values contained in the healing mantras of the Malay community of Mepar Village, Lingga District, Lingga Regency. The method used in this study is descriptive qualitative. The instrument in this study is the researcher herself as the main instrument, supported by observation guidelines and interview guidelines. The data in this study are in the form of healing mantra texts and interview results obtained from informants in Mepar Village, Lingga District, Lingga Regency. The data collection techniques used to obtain the research data are observation, interview, and documentation techniques. The data analysis technique used in this study is the interactive qualitative data analysis technique through the stages of data reduction, data presentation, and conclusion drawing. The results of the research show that the healing mantras of the Malay community of Mepar Village contain seven social values, namely religious values such as the recitation of basmalah and prayers to Allah Swt. that always accompany every mantra, social solidarity values such as the community's mutual help during the healing process, care and helping values such as the willingness of the traditional healer to help anyone in need regardless of the patient's status or background, local wisdom values such as the use of distinctive Malay diction, symbols, and natural materials in the mantras, community trust values such as the belief that still persists toward the efficacy of the mantras as a means of healing, moral and social ethics values such as the rules binding both the mantra reader and the patient being helped, and cultural preservation values such as the effort to maintain and pass down the healing mantras from generation to generation.